2016
DOI: 10.3892/etm.2016.3326
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment of premature ovarian failure in a mouse model via stimulation of the Notch-1 signaling pathway

Abstract: Premature ovarian failure (POF) is a condition affecting 1% of women in the general population, causing amenorrhea, hypergonadotropism and hypoestrogenism before the age of 40. Currently, POF cannot be reversed and, although treatments are available, there is an urgent need for improved treatment strategies. Growth hormone (GH) is a pleiotropic hormone that affects a broad spectrum of physiological functions, from carbohydrate and lipid metabolism to the immune response. GH has previously been used to treat PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…HOTAIR overexpression inhibits the apoptosis of hamster ovarian cells. Notch-1 overexpression has been reported to inhibit the apoptosis of various cancers, while activation of Notch-1 signaling has been demonstrated to be an effective treatment for premature ovarian failure (13). In the present study, HOTAIR overexpression significantly inhibited the apoptosis of hamster ovarian cells compared with control cells (P<0.05; Fig.…”
Section: Hotair Overexpression Promotes Notch-1 Expression In Two Norsupporting
confidence: 55%
See 1 more Smart Citation
“…HOTAIR overexpression inhibits the apoptosis of hamster ovarian cells. Notch-1 overexpression has been reported to inhibit the apoptosis of various cancers, while activation of Notch-1 signaling has been demonstrated to be an effective treatment for premature ovarian failure (13). In the present study, HOTAIR overexpression significantly inhibited the apoptosis of hamster ovarian cells compared with control cells (P<0.05; Fig.…”
Section: Hotair Overexpression Promotes Notch-1 Expression In Two Norsupporting
confidence: 55%
“…The results of a previous study revealed that activation of the Notch-1 signaling pathway is important for the recovery of premature ovarian failure in mice (13). It is also well known that HOTAIR interacts with the Notch pathway to exert its biological functions (19).…”
Section: Discussionmentioning
confidence: 99%
“…The low expression of inl3 supported this hypothesis. Previous studies provided evidence for our hypothesis . For instance, growth hormone promoted oocyte maturation via activation of the notch signaling pathway in ovarian tissue .…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies provided evidence for our hypothesis . For instance, growth hormone promoted oocyte maturation via activation of the notch signaling pathway in ovarian tissue . The notch pathway was activated during spermatogenesis in the mouse .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation